2006
DOI: 10.1097/01.tp.0000225772.22757.5e
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin Delays But Does Not Prevent Recovery from Acute Renal Failure: Role of Acquired Tubular Resistance

Abstract: Rapamycin delays but does not prevent renal recovery after ARF. MPT cells become resistant to rapamycin after prolonged exposure. We speculate that the ultimate recovery of renal function after ARF is due to the development of acquired tubular cell resistance to rapamycin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
39
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 33 publications
9
39
2
1
Order By: Relevance
“…17 mTOR phosphorylates and inhibits the kinases ULK1/2, catalytic subunits of a protein kinase complex that initiates the autophagic cascade. 26,27 Similar to reports by Lieberthal et al, 28,29 we showed activation of mTORC1 in the proximal tubules of the postischemic kidneys. At 3 days after IRI, cells with mTORC1 activation had fewer RFP puncta.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…17 mTOR phosphorylates and inhibits the kinases ULK1/2, catalytic subunits of a protein kinase complex that initiates the autophagic cascade. 26,27 Similar to reports by Lieberthal et al, 28,29 we showed activation of mTORC1 in the proximal tubules of the postischemic kidneys. At 3 days after IRI, cells with mTORC1 activation had fewer RFP puncta.…”
Section: Discussionsupporting
confidence: 78%
“…These results are consistent with the study showing that rats receiving rapamycin treatment had a lower rate of tubular proliferation and delayed recovery of renal function after ischemic injury. 28 In mice with cisplatininduced AKI, however, rapamycin treatment led to a modest but statistically significant reduction in BUN and creatinine and a better renal morphology. The beneficial effect was related to the increase in LC3-II levels at 2 days after cisplatin injection, suggesting that early activation of autophagy during the injury phase protected against chemical toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…However, by day 7 after IRI induction there was no significant difference in BUN level between experimental groups. Similar effects have been reported in the work of Lieberthal et al [27], who found no differences in kidney function on day 7 after induced IRI between non-treated and rapamycin-treated rats, but by day 6 after induced IRI, rapamycin-treated animals had lower GFR and worse histology score. It is important to note that when renal function was explored 30 days after induced renal IRI in rats, it was found that rapamycin prevented GFR decline [28].…”
Section: Discussionsupporting
confidence: 75%
“…This finding is in line with a recent report demonstrating reduced cytoprotective capacity under everolimus treatment in I/R in rats (36). In the 48 h after I/R, mTORC1-deficient tubules showed a reduced proliferative response, corresponding with the documented delayed graft function in kidney transplant patients treated with mTORC1 inhibitors (20,21).…”
Section: Discussionsupporting
confidence: 81%
“…Mice treated with rapamycin can develop a Fanconi-like proximal tubular injury pattern consisting of glucosuria, amino aciduria, and phosphaturia (19), whereas renal transplant patients receiving mTOR inhibitors early after transplantation experience increased rates of delayed graft function (20). A prolonged recovery after ischemia/reperfusion (I/R) injury also is observed commonly in animals treated with rapamycin (21). Despite the assumption that these perturbations are related to the direct effects of mTOR inhibitors on tubular epithelial cells in the kidney, it has been difficult to differentiate these findings from the systemic effects of mTOR inhibitors.…”
mentioning
confidence: 99%